综合考虑运动仿真结果的曲柄滑块机构的优化设计 - 陈赛克; 刘江涛 (Jixie chuandong)
The crank-slider mechanisms are designed parametrically based on by MSGC and some analytic results were obtained. By simulating their movement, slider’s location, velocity and acceleration and link’s turn angle, angle velocity and angle acceleration could be analyzed. It is showed that slider’s acceleration and link’s angle acceleration could be reduced by increasing the setover and length of the link. Based on the results of simulate, the optimal design project was selected among them. The difficulty of analysis can reduce consumedly by using MSGC and the efficiency and veracity of analysis can be elevated.